Tinjauan Literatur Analisis Perbandingan Karakteristik Fisik dan Stabilitas Sediaan Krim Topikal Tipe Oil in Water (O/W) dan Water in Oil (W/O) - Brilyan Dwi Kristianto; Elvina Putri Rahmawati; Stella Reflya Pramudita; Varis Sanaila Salsabila (Journal of Educational Innovation and Public Health, 2026)
This review article evaluates the physical characteristics and stability of Oil in Water (O/W) and Water in Oil (W/O) creams through a comparative literature study published between 2021 and 2026. The evaluation focuses on important parameters, including viscosity, spreadability, adhesion, pH, and accelerated stability testing. The findings reveal that O/W creams generally have lower viscosity and greater spreadability, making them more suitable for daily cosmetic and therapeutic applications due to their lighter texture and better aesthetic acceptance. In contrast, W/O creams demonstrate higher physical stability, stronger adhesion, and superior occlusive properties, which are beneficial for protecting sensitive active ingredients and maintaining skin hydration over longer periods. The differences in performance are strongly influenced by the optimization of emulsifier Hydrophilic-Lipophilic Balance (HLB) values and the ratio between oil and water phases. Both cream types show good biocompatibility with skin pH ranging from 4.5 to 6.5, indicating their safety and effectiveness for topical pharmaceutical and cosmetic formulations.